Laundering of Proceeds of Crime Asset Tax - Caro Coria, Dino Carlos (2015)
Although many legal systems criminalizing the laundering of assets derived from a tax crime, in accordance with the principles of the FATF and other international bodies, in this contribution it is argued that the space for the commission of these forms of washing is quite small. insofar as is not acceptable the thesis of the pollution of the total assets of the fraudster, the scale of money laundering is conditioned, as in all cases of laundering, to secure identification, with the minimal evidentiary guarantees of specific goods that come from a previous crime. if this is added to the prescription of tax crime and to the called tax adjustment, it originates the decontamination of the material object, then the scope of these forms of laundering is even more limited. Furthermore, this group of crimes provides a fertileground for strict interpretations, or even restricted, accorded to the objective imputation, as seen for example in the treatment of cases of goods mix.